1999
DOI: 10.1097/00000658-199911000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor and Its High-Affinity Receptor in Chronic Pancreatitis

Abstract: ObjectiveTo study the mechanisms that are involved in nerve growth and contribute to pain generation in chronic pancreatitis (CP). Summary Background DataChronic pancreatitis is a painful disease associated with characteristic nerve changes, including an increase in nerve number and diameter. The mechanisms that influence nerve growth are not known. Nerve growth factor (NGF) and its high-affinity tyrosine kinase receptor A (TrkA) are involved in neural development and survival and growth of central and periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(107 citation statements)
references
References 40 publications
6
100
0
1
Order By: Relevance
“…In addition to the role of NGF in bladder function, it has also been identified as a key molecule in the signaling of pain during inflammation (1,17,23,24,26,61). Visceral inflammation is often accompanied by an increase in sensitivity of somatic structures to noxious stimuli, commonly called referred hyperalgesia (9,75).…”
Section: Increased Somatic Sensitivity After Rvsmentioning
confidence: 99%
“…In addition to the role of NGF in bladder function, it has also been identified as a key molecule in the signaling of pain during inflammation (1,17,23,24,26,61). Visceral inflammation is often accompanied by an increase in sensitivity of somatic structures to noxious stimuli, commonly called referred hyperalgesia (9,75).…”
Section: Increased Somatic Sensitivity After Rvsmentioning
confidence: 99%
“…It does not cross-react with other neurotrophin receptors (Trk-B or Trk-C). These two antibodies have been characterized by immunocytochemistry and functional assay [17,19,47,48].…”
Section: Rna Preparation and Rt-pcr Analysis Of Ngf Gp140mentioning
confidence: 99%
“…The process can lead to ischemia and local changes in the gut which by themselves can cause pain, but there is also destruction of the nerves, and therefore neuropathic pain features are likely prevalent (for review see 24). As outlined later in this chapter several recent articles have demonstrated upregulation of signalling molecules involved in inflammation and pronociceptive mediators, but also neurotropic factors in the pancreatic parenchyma in patients with CP (31). Increased neural density and hypertrophy, sprouting and neuritis of the intrapancreatic nerves, as well as activation of glia and immune cells have also been reported in pancreatic tissue from the patients (11).…”
Section: Pain Pathogenesismentioning
confidence: 99%
“…Systematic analysis of human CP tissues revealed that intrapancreatic nerves are enlarged in the resected inflammatory mass, irrespective of the etiology of the CP (30). These neuroplastic alterations during pancreatic neuropathy seem to have an impact on the clinical course of the disease, because the extent of neuroplasticity is closely correlated to the severity of pain in CP patients (31). On the other hand, neuro-inflammation is a characteristic feature of neuropathic pain syndromes (54).…”
Section: Morphological Alterationsmentioning
confidence: 99%
See 1 more Smart Citation